2013
DOI: 10.1101/gad.219642.113
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy suppresses progression of K-ras-induced lung tumors to oncocytomas and maintains lipid homeostasis

Abstract: Macroautophagy (autophagy hereafter) degrades and recycles proteins and organelles to support metabolism and survival in starvation. Oncogenic Ras up-regulates autophagy, and Ras-transformed cell lines require autophagy for mitochondrial function, stress survival, and engrafted tumor growth. Here, the essential autophagy gene autophagy-related-7 (atg7 ) was deleted concurrently with K-ras G12D activation in mouse models for non-smallcell lung cancer (NSCLC). atg7-deficient tumors accumulated dysfunctional mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
574
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(614 citation statements)
references
References 35 publications
32
574
7
1
Order By: Relevance
“…26 In a separate study, it was also demonstrated that the loss of Atg5 or Atg7 could also prevent the development of high-grade pancreatic neoplastic legions induced by K-ras, and the pancreatic tumor growth could be restored if the expression of p53 was also abolished. 27 These recent findings together with ours indicate that autophagy is required for tumor progression for at least three different tumor types and that the deletion of p53 can partially restore tumorigenesis when autophagy is impaired.…”
Section: Discussionmentioning
confidence: 97%
“…26 In a separate study, it was also demonstrated that the loss of Atg5 or Atg7 could also prevent the development of high-grade pancreatic neoplastic legions induced by K-ras, and the pancreatic tumor growth could be restored if the expression of p53 was also abolished. 27 These recent findings together with ours indicate that autophagy is required for tumor progression for at least three different tumor types and that the deletion of p53 can partially restore tumorigenesis when autophagy is impaired.…”
Section: Discussionmentioning
confidence: 97%
“…26 The core autophagy machinery may be protected from alteration in some human cancers, an idea supported by recent studies in murine models of lung cancer that find autophagy to be essential for tumor progression. 27,28 Importantly, we found that clustering abundance profiles of AA genes stratified patient OS in 3 of 9 cancer types and grouped patients with similar pathophysiology together, linking the differential expression of autophagy regulators and interactors to clinical features known to influence patient outcome. This suggests that clinically relevant differential pathway activities exist between …”
Section: Discussionmentioning
confidence: 97%
“…72 Autophagy has been shown to support tumorigenesis in lung cancer, particularly in KRAS-driven lung cancer cell lines and animal models that may be addicted to high levels of autophagy, 73,74 and autophagy inactivation in KRasdriven mouse models of lung cancer impairs cell growth, proliferation, and tumor progression. 27,28 We stratified gene expression of all 211 AA genes in both LUAD and LUSC by known recurrent somatic disease-specific alterations, including EGFR and KRAS alterations, and did not find differences in core gene expression between altered and wild-type patients; however, LUSC patients with EGFR amplification had increased mRNA levels of NFE2L2 (median FC > 2; Table S5). Both overactive and impaired autophagy are hypothesized to support oncogenic NFE2L2 activity in cancer, 75 through increased degradation of the NFE2L2 sequestering protein KEAP1 51 or through reduced degradation of KEAP1 binding protein SQSTM1/p62, 76 respectively.…”
Section: Clear Cell Renal Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested to hold a tumour suppressive function during early tumourigenesis, [20][21][22][23][24][25][26][27] whereas it can also sustain cancer progression. [28][29][30][31][32][33][34][35][36] Increased levels of basal autophagy have been found in a variety of cancer tissues including colorectal cancer (CRC), where autophagy supports tumour growth and confers tumour aggressiveness. 31 Autophagy is inhibited by oncogenic tyrosine kinases (OncTKs) and receptor tyrosine kinases (RTKs) via activation of the PI3K/AKT/mTORC1 and RAS/MAPK signalling.…”
Section: Introductionmentioning
confidence: 99%